Fikih Ekowisata Berbasis Maqasid al-Syari’ah (Studi Pengelolaan Wisata Alam Hutan Mangrove di Wonorejo Kota Surabaya) - Mufid, Moh (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
This article aims to construct ecotourism jurisprudence (fiqh) based on maqÄá¹£id syarÄ«â€™ah. Management of mangrove ecotourism in Wonorejo Surabaya city uses a conservation and society participation approach to ensure the mangrove forest ecosystem is sustainable. In the perspective of the maqÄá¹£id syarÄ«â€™ah the management of sustainable ecotourism is in line with the philosophical spirit in the following objectives of Shariâ€™a: (1) á¸¥ifáº“ al-mÄl in the context of mangrove ecotourism to empower local communities in the economic field, (2) á¸¥ifáº“ al-bÄ«â€™ah in the context of mangrove ecotourism requires the protection of ecological aspects, and (3) á¸¥ifáº“ al-â€˜aql in the context of ecotourism functions as a learning medium in the world of science development education. Jurisprudence for ecotourism as an idea that relies on a normative and empirical approach to the utilization of mangrove forests as natural tourism is expected to be able to provide insight to visitors to be eco-friendly. The construction of ecotourism jurisprudence can be formulated by considering the following aspects: the first, the orientation of ecotourism must be built with the aim of preserving the mangrove ecosystem; the second, management of mangrove ecotourism based on an analysis of the benefits of ecological, economic and educational aspects; the third, the development of mangrove ecotourism does not conflict with shariâ€™a principles; the fourth, management of mangrove ecotourism based on the permission of stakeholders; the fifth, community involvement in the preservation of mangrove forest tourism is a collective obligation (fará¸u kifÄyah).